2021
DOI: 10.1080/09515089.2021.1946026
|View full text |Cite
|
Sign up to set email alerts
|

What’s up with anti-natalists? An observational study on the relationship between dark triad personality traits and anti-natalist views

Abstract: In the past decade, research on the dark triad of personality (Machiavellianism, narcissism, and psychopathy) has demonstrated a strong relationship to a number of socially aversive moral judgments such as sacrificial utilitarian decisions in moral dilemmas. This study widens the scope of this research program and investigates the association between dark triad personality traits and anti-natalist views, i.e., views holding that procreation is morally wrong. The results of this study indicate that the dark tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…We were agnostic as to which direction the effect would run with either type of empathy. On the one hand, previous research found a positive relationship of antinatalism to dark triad traits (and as such low empathy; Schönegger, 2021), though there is also a plausible explanation of expecting antinatalists to be exceptionally high in empathy which plays out in their concern for the unborn generation. Because we failed to find a significant relationship to cognitive empathy but did find a statistically significant negative relationship to affective empathy, we take these data to speak in favor of the former possibility.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…We were agnostic as to which direction the effect would run with either type of empathy. On the one hand, previous research found a positive relationship of antinatalism to dark triad traits (and as such low empathy; Schönegger, 2021), though there is also a plausible explanation of expecting antinatalists to be exceptionally high in empathy which plays out in their concern for the unborn generation. Because we failed to find a significant relationship to cognitive empathy but did find a statistically significant negative relationship to affective empathy, we take these data to speak in favor of the former possibility.…”
Section: Discussionmentioning
confidence: 92%
“…First, those high in empathy may be more sensitive to the risks of causing suffering by bringing life into this world, thus standing in a positive relationship to antinatalism. Second, this relationship may also be negative, as it has been previously found that that those low on empathy (i.e., high in dark triad traits) are more likely to hold antinatalist views (Schönegger, 2021). Therefore, we aimed to investigate which of these two potential relationships of antinatalism and empathy was empirically better supported and did not make a directional prediction.…”
Section: Studymentioning
confidence: 99%
See 3 more Smart Citations